Non-visual Opsins and Novel Photo-Detectors in the Vertebrate Inner Retina Mediate Light Responses Within the Blue Spectrum Region - Guido, Mario Eduardo (2020)
In recent decades, a number of novel non-visual opsin photopigments belonging to the family of G protein- coupled receptors, likely involved in a number of non-image-forming processes, have been identified and characterized in cells of the inner retina of vertebrates. It is now known that the vertebrate retina is composed of visual photoreceptor cones and rods responsible for diurnal/color and nocturnal/black and white vision, and cells like the intrinsically photosensitive retinal ganglion cells (ipRGCs) and photosensitive horizontal cells in the inner retina, both detecting blue light and expressing the photopigment melanopsin (Opn4). Remarkably, these non-visual photopigments can continue to operate even in the absence of vision under retinal degeneration. Moreover, inner retinal neurons and Müller glial cells have been shown to express other photopigments such as the photoisomerase retinal G protein-coupled receptor (RGR), encephalopsin (Opn3), and neuropsin (Opn5), all able to detect blue/violet light and implicated in chromophore recycling, retinal clock synchronization, neuron-to-glia communication, and other activities. The discovery of these new photopigments in the inner retina of vertebrates is strong evidence of novel light-regulated activities. This review focuses on the features, localization, photocascade, and putative functions of these novel non-visual opsins in an attempt to shed light on their role in the inner retina of vertebrates and in the physiology of the whole organism.